1981
DOI: 10.1161/01.cir.63.1.70
|View full text |Cite
|
Sign up to set email alerts
|

Failure of antiarrhythmic drugs to prevent experimental reperfusion ventricular fibrillation.

Abstract: SUMMARY Ninety-nine adult mongrel dogs underwent acute ligation of the proximal left anterior descending coronary artery. Thirty minutes later, the occlusion was released to evaluate the effectiveness of five antiarrhythmic protocols in eliminating reperfusion ventricular fibrillation. The five protocols included: protocol 1 -i.v. lidocaine, preligation and prerelease (n = 19); protocol 2 i.v. lidocaine, prereperfusion only (n = 22); protocol 3 chronic, oral, daily amiodarone for 2 weeks preligation (n = 19); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0

Year Published

1982
1982
2005
2005

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(16 citation statements)
references
References 52 publications
4
12
0
Order By: Relevance
“…However, when pentobarbital sodium was used as an anesthetic, d-sotalol as well as MS-551 were effective in suppressing the VF. Although the rate of occurrence of reperfusion VF was not high (59% in all 32 control beagles of the present study) and variable as has already been reported (21), the suppression of VF by these drugs might be related to the prolongation of the refractory period. It is because new class III antiarrhythmic drugs are reported not to suppress either cardiac Na or Ca channels and thus had no antiarrhythmic effects on automaticity arrhythmias such as those produced by two-stage coronary ligation or digitalis in dogs (6).…”
Section: D-sotalol In Halothane Anesthetized Beaglessupporting
confidence: 52%
See 1 more Smart Citation
“…However, when pentobarbital sodium was used as an anesthetic, d-sotalol as well as MS-551 were effective in suppressing the VF. Although the rate of occurrence of reperfusion VF was not high (59% in all 32 control beagles of the present study) and variable as has already been reported (21), the suppression of VF by these drugs might be related to the prolongation of the refractory period. It is because new class III antiarrhythmic drugs are reported not to suppress either cardiac Na or Ca channels and thus had no antiarrhythmic effects on automaticity arrhythmias such as those produced by two-stage coronary ligation or digitalis in dogs (6).…”
Section: D-sotalol In Halothane Anesthetized Beaglessupporting
confidence: 52%
“…d-Sotalol was infused intravenously at a speed of 10 mg/kg/hr. Since the incidence of occurrence of coronary ligationreperfusion arrhythmias is known to be quite variable (21), experiments were randomized using a pair of beagles (by coin-flip); one received the drug infusion, and the other received 0.9% NaCI (saline) infusion. The speed of infusion was 1 ml/min.…”
mentioning
confidence: 99%
“…However, several recent studies in in situ hearts and isolated tissues have suggested that both reentry and oscillatory afterpotentials (delayed afterdepolarizations) may be involved in the generation of these arrhythmias, [7][8][9][10] Verapamil, a slow channel inhibitor, has been demonstrated to be effective in preventing arrhythmias in experimental ischemia.11-15 However, contradictory observations have been reported with respect to verapamil's efficacy in preventing reperfusion arrhythmias. 4,[16][17][18][19][20] The mechanisms by which verapamil might suppress reperfusion arrhythmias are even less clear. Verapamil was found to suppress reperfusion-induced oscillatory From The goals of the present investigation were to evaluate the potential efficacy of verapamil against reperfu-sion-induced arrhythmias in this model and to determine the electrophysiological actions that accompany antiarrhythmic efficacy.…”
Section: Verapamil Prevents Slowing Of Transmural Conduction and Suppmentioning
confidence: 99%
“…These "reperfusion arrhythmias" are particularly severe and frequently fatal since they often progress to ventricular fibrillation. They also seem to be resistant to standard antiarrhythmic therapy (Naito, et al, 1981), suggesting that their aetiology may vary from that of arrhythmias observed during myocardial ischaemia. Since thromboxane has been implicated in coronary vasospasm in patients with variant angina (Lewy etal., 1979) it may also be involved in the reperfusion arrhythmias which can occur when spasm is reversed.…”
Section: Introductionmentioning
confidence: 99%